Text and image in medieval Persian art - Blair, Sheila (Edinburgh studies in Islamic art., 2014)
"Investigates the interaction between word and image in medieval Persian art. Focusing on 5 objects found in the main media at the time -- ceramics, metalwares, painting, architecture and textiles -- Sheila S. Blair shows how artisans played with form, material and decoration to engage their audiences. She also shows how the reception of these objects has changed and that their present context has implications for our understanding of the past. Greater Iranian arts from the 10th to the 16th century are technically some of the finest produced anywhere. They are also intellectually engaging, showing the lively interaction between the verbal and the visual arts."--